Zadania mediacyjne w materiałach do uczenia się i nauczania języka polskiego jako obcego w perspektywie CEFR – Companion Volume - Janowska, Iwona (Neofilolog, 2026)
Mediation is recognised in the Common European Framework of Reference for Languages (2001) as one of the four modes of communication, alongside reception, production and interaction. In mediation activities, the learner acts as an intermediary, enabling communication across linguistic, cultural and technical barriers. Despite the important role of mediation in multilingual and intercultural environments, teaching materials rarely focus on developing these competences. The aim of the present study was to determine whether and to what extent mediation activities are developed in textbooks for teaching Polish as a foreign language, with reference to the categories of mediation of text, concepts and communication defined in the CEFR – Companion volume (2020). A qualitative analysis was used to categorise the tasks and exercises in selected textbooks. Conclusions and recommendations are formulated, based on the interpretation of the content of the task instructions.